2015
DOI: 10.1007/s11589-015-0109-0
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of subsurface density variations before the 4.20 Lushan M S7.0 earthquake in the Longmenshan area: inversion results

Abstract: The 4.20 Lushan M S 7.0 earthquake occurred on the southwest segment of the Longmenshan fault on 20 April 2013. Some meaningful information on the preparation and occurrence of this earthquake was found based on the dynamic variation of gravity (DVG). To examine the great progress of the Lushan earthquake, we obtained the density variation (DENV) derived from the DVG using the compact gravity inversion method in this article. The inversion results reveal three main findings: (1)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…In the absence of suitable prior constraints, the solution of gravity potential field inversion has low vertical resolution, and is not unique. Since several previous studies have found gravity changes before the M S 7.0 Lushan earthquake [26][27][28] , we fixed the inversion depth at the focal depth. Unlike the classic gravity potential inversion method 65 , the BADI method solve the non-unique problem by carrying out inversion and optimization of model parameters based on the time-varying gravity observation data under some prior constraints (Supplementary method 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the absence of suitable prior constraints, the solution of gravity potential field inversion has low vertical resolution, and is not unique. Since several previous studies have found gravity changes before the M S 7.0 Lushan earthquake [26][27][28] , we fixed the inversion depth at the focal depth. Unlike the classic gravity potential inversion method 65 , the BADI method solve the non-unique problem by carrying out inversion and optimization of model parameters based on the time-varying gravity observation data under some prior constraints (Supplementary method 1).…”
Section: Methodsmentioning
confidence: 99%
“…The epicenter of the M S 7.0 Lushan earthquake was in the northern section of the Sichuan THRGO network. Several previous studies have reported gravity changes before the M S 7.0 Lushan earthquake based on the THRGO dataset [26][27][28] . However, how the gravity change relates to the mechanism of the Lushan earthquake occurrence remains debated.…”
mentioning
confidence: 99%
“…Based on the de nition of equivalent water height in satellite gravity measurement, the BADI method employs an apparent density model to μGal μGal construct a relationship between the deep eld source body and the surface observed gravity changes. Unlike the classic gravity potential inversion method (Last and Kubik, 1983;Xuan et al, 2015), the BADI method solve the non-unique problem by carrying out inversion and optimization of model parameters based on the time-varying gravity observation data under some prior constraints (Text S1).…”
Section: Apparent Density Modelingmentioning
confidence: 99%
“…The epicenter is located in the northern section of the Sichuan THRGO network. Several previous studies have reported that there are signi cant gravity changes before the M S 7.0 Lushan earthquake based on the THRGO dataset (Zhu et al, 2013;Hao et al, 2015;Xuan et al, 2015). However, how the gravity change relates to the mechanism of the occurrence of Lushan earthquake remains debated.…”
Section: Introductionmentioning
confidence: 99%
“…As a tentative research, Xuan et al . 20 suggested that the crustal DCs derived from the temporal-spatial gravity-change data may imply the dynamic information related to the pre-earthquake.…”
Section: Introductionmentioning
confidence: 99%